A Rare Case of Xanthogranulomatous Pyelonephritis with Spontaneous Renocolic Fistula and IVC Thrombosis - Daniele Sforza; Leandro Siragusa; Matteo Ciancio Manuelli; Linda De Luca; Bruno Sensi; Simona Grande; Renato Argirò; Marco Nezzo; Massimo Villa; Michele Grande (Case Reports in Nephrology)
Xanthogranulomatous pyelonephritis (XGPN) is a rare disorder affecting the kidney which can fistulise to the colon in exceptional cases. We herein report a case of XGPN with renocolic fistula and large vessel thrombosis presenting with sepsis and pulmonary embolism. Preoperative diagnosis and strategic planning resulted in successful management. A 64-year-old woman presented to the emergency department with abdominal pain and a septic condition, corroborated by venous thromboembolism. Workup diagnosed a left renal abscess with calicocolic fistula. Scintigraphy confirmed a nonfunctioning left kidney. The patient underwent inferior vena cava filter placement and staged surgery. The first, damage control procedure was a loop ileostomy. Ten days later, when the patient’s conditions improved, she underwent left nephrectomy and left colectomy with primary anastomosis. Finally, a year later, the ileostomy was closed. At follow-up, the patient was well, with unremarkable renal function. Scrupulous diagnostics, multidisciplinary decision making, and staged intervention have been key to optimal outcome.